Probabilistic seismic hazard assessment for Taiwan: Updates and improvements in TEM PSHA2025 - Jia-Cian Gao; Jo-Chen Kao; Chung-Han Chan; Ray Y. Chuang; Cheng-Hung Chen; J. Bruce H. Shyu; Kuo-En Ching; Yu Wang; Kuo-Fong Ma (Engineering Geology, 2026)

Acute Stress Drives Adaptive Anxiety via Excitatory-Inhibitory Imbalance in the Prefrontal-Amygdala Circuit in Male Mice - Jia-Xin Zou; En Cao; Zhi-Hao Wang; Rui Han; Xing-Yan Lu; Cheng-Yuan Huang; Xia Qin; Wei-Zhu Liu; Wen-Hua Zhang; Bing-Xing Pan (Neuroscience Bulletin, 2026)

Analyte–electrode interactions and analytical performance of electrochemical-SERS in complex food matrices - Heera Jayan; Ruiyun Zhou; Limei Yin; En Han; Chen Wang; Xiaobo Zou; Zhiming Guo (Critical Reviews in Food Science and Nutrition, 2026)

Strengthening water-energy-food security through interconnected systems: A nexus perspective - En Hua; Xinxueqi Han; Chenhao Zhang; Xuhui Wang; Shikun Sun; Bing Wang; Yubao Wang (Journal of Cleaner Production, 2026)

Bimetallic metal-organic frameworks-modified hybrid capacitive deionization for enabling concurrent desalination and antibiotic resistance genes removal - Ziwei Chen; Zhanming Tan; Xuefeng Liu; Peilin Han; Di Zhang; Mengqi Jiang; En Xie; Yunkai Li (Desalination, 2026)

Multifunctional carbon-based materials for corrosion resistance in aviation: A comprehensive review - Xiaoshun Zhang; Fuchun Liu; En-Hou Han (Chemical Engineering Journal, 2026)

Life cycle environmental impact of customer premises equipment: insights from a Wi-Fi router case study - Hsin-Tien Lin; Kuo-Che Weng; En-Yu Yeh; Chun-Wei Wang; Han-Chang Pan (The International Journal of Life Cycle Assessment, 2026)

AtGASA1 positively regulates Arabidopsis response to salt stress by suppressing accumulation of reactive oxygen species - Jian-Bo Song; Hao-En He; Cai-Feng Wang; Xian-Zhi Zuo; Zi-Xin Zhao; Ya-Ru Li; Yu-Fan Chen; Shu-Fan Liu; Han-Wen Guo; Xuan Huang (Plant Cell Reports, 2026)

A national-scale early detection and rapid response (EDRR) to invasive cane toads (Rhinella marina) in Taiwan - Yung-Chih Lai; Chun-Fu Lin; Li-Mien Tseng; Cheng-En Li; Jia-Han Lee; Jou-Yun Chen; Ming-Chih Wang; Chun-Hung Lai; Yueh-Feng Chen; Chun-Lin Ho; Wei-Chun Cheng; Yi-Ju Yang (Biological Invasions, 2026)

Novel biodiversity and biogeography insights of filamentous Bangiales (Rhodophyta) from China - Yan-De Wang; Yin-Yin Deng; Cui-Cui Tian; Han-Ru Ge; Wei Zhou; Nan-Jing Ji; Li-En Yang (Algae, 2026)
The taxonomy of filamentous Bangiales was challenging due to its plastic and simple morphology. Molecular approaches play a significant role in revealing cryptic biodiversity and resolving phylogenetic relationships. Nonetheless, the biodiversity of filamentous Bangiales in many regions, including China, has not been thoroughly investigated yet using updated methods. In this study, we investigated the biodiversity of filamentous Bangiales in China, employing a more comprehensive and detailed sampling approach. The rbcL and 18S gene sequences (partial or complete) of 49 specimens collected from 37 sites were obtained. Phylogenetic analysis resolved these specimens into four clades, including Bangia, ‘Bangia’ 1, ‘Bangia’ 2, and Pseudoganglia. Seven putative species were delineated using empirical methods, including Automatic Barcode Gap Discovery (ABGD), General Mixed Yule Coalescent (GMYC), and Bayesian Poisson tree processes (bPTP), as well as genealogical analysis. Among them, four were species previously reported, two were cryptic species, and the other was a new record in China. The distribution of these molecularly delineated species was mapped along China’s coastline. Similar to the bladed Bangiales, antitropical, transoceanic, and thermal-gradient distribution patterns were also observed for filamentous Bangiales on a global scale. The ancestral region was retraced by incorporating species data from China into existing datasets using BioGeoBEARS with BAYAREALIKE + J as the best-supported model. Under this model, East Asia shows the highest marginal probability as the ancestral area for the crown clade, though uncertainty remains across alternative regions. A most parsimonious expansion scenario of Bangiales from east Gondwana to other regions of the world was proposed.

Synergistic co-preintercalation of nickel and aluminum ions into vanadium oxide hydrate as positive electrode material in ultrahigh-rate and high-capacity aqueous zinc-ion batteries - Hung-Lin Chen; Tsung-Yi Chen; En-Hao Li; Yen-Lin Chen; Wen-Hsuan Lu; Hsu-Chen Cheng; Shu-Yu Chen; Jue-Hua Pan; Hsiang-Jung Chen; Syuan-Cen Lin; Ruey-An Doong; Sanna Gull; et al. (Chemical Engineering Journal, 2026)

Unveiling Mo doping effects in hydrated vanadium oxide cathodes for high-energy zinc-ion batteries: Evidence from operando synchrotron X-ray and DFT analysis - Sanna Gull; Hsu-Chen Cheng; En-Hao Li; Tsung-Yi Chen; Chung-Sheng Ni; Wan-Ju Yu; Hao-Hsiang Chang; Ai-Yin Wang; Ruey-An Doong; Chin-Lung Kuo; Yu-Chun Chuang; Bo-Hao Chen; et al. (Chemical Engineering Journal, 2026)

Disease outbreaks substantially enhance greenhouse gas emissions from Asian seabass (Lates calcarifer) aquaculture pond - Han-Yang Yeh; Chien-Wei Tu; Yi-Jung Chen; Wen-Ping Cheng; Pei-Yu Shih; Chia-Chia Yu; Wei-Sheng Zhang; Wei-En Hung; Yu-Ru Lin; Zhen Hao Liao; Wen-Chen Chou; Hsiao-Chun Tseng; et al. (Marine Pollution Bulletin, 2026)

Deciphering the effects of cascade reservoirs on phytoplankton communities in a karst river: Importance of super-large reservoirs - Jiang Wu; Xiao-Nan Wu; Xiao-Hui Zhao; Xu Han; En-Hang Liang; Rui An; Jia-Ju Liu; Wei-Ling Sun; Nan Xu; Ting Wang (Journal of Environmental Management, 2026)

Biomimetic enzyme electrochemical sensor based on nanocomposites of carbon black coated ZnO nanoflowers/poly (L-phenylalanine) for food colorant analysis - En Han; Ming Bao; Yang Li; Xiaoya Dong; Jianrong Cai (Food Bioscience, 2026)

Deciphering water-energy-food synergies through a multi-level symbiosis framework: Insights from the Yellow River Basin - Xinxueqi Han; En Hua; Xinchun Cao; Bernie A. Engel; Shikun Sun; Yubao Wang (Agricultural Systems, 2026)

Dual-enhanced multifunctional molecularly imprinted electrochemical sensor with specificity and signal amplification for tartrazine analysis - En Han; Ming Bao; Yang Li; Jianrong Cai (Food Chemistry, 2025)

Corrigendum to “Assessing CO₂ sources and sinks in and around Taiwan: Implication for achieving regional carbon neutrality by 2050” [Mar. Pollut. Bull. 206 (2024) 116664]. - Chin-Chang Hung; Hsueh-Han Hsieh; Wen-Chen Chou; En-Chi Liu; Chun Hoe Chow; Yi Chang; Tse-Min Lee; Peter Hans Santsch; R.R.M.K.P. Ranatunga; Hernando P. Bacosa; Yung-Yen Shih (Marine Pollution Bulletin, 2025)

Regulating charge separation by structure adjusting in pyrene-based 1D COFs for efficient photocatalytic hydrogen evolution - Bing Han; Shuyan Wang; Xianglin Yu; Xuxin Fan; En Liang; Yao Yang; Huan Zhang; Changyu Qin; Junbo Li (Chemical Engineering Journal, 2025)

A neutral multivalent AIE–TICT scaffold: An off-on, wash-free fluorogenic strategy for biosensing glycan–protein interactions in live cells and mycobacteria - Huai-En Chang; Chien-Chin Chen; Yi-Jin You; Pei-Hsuan Lee; Bo-Chang Ruan; Hong-Luen Kwok; Ching-Tse Wu; Chuang-Rung Chang; Jiun-Han Chen; Eugene C. Lin; Pei-Jhen Li (Analytica Chimica Acta, 2025)

Dry cleaning of food-grade plastics on a gas-solid biphase fluidized bed: Efficiency, assessment and mechanism - Ziyang Liu; Cong-Cong Zhang; Fu-Shen Zhang; Shi-Lei Han; Dai-En Yang (Journal of Environmental Chemical Engineering, 2025)

Bacteria in the Phylum Bacillota Degrade Nicotine Through the Variant of Pyridine and Pyrrolidine Pathway - Xiu-Ming Liu; Xuan Hai; Cong-Jian Li; Yu-Fan Han; Xing Chen; Yu-Jin Fan; Jian Wu; En-Min Zhou; Yuan-Dong Li; Ling-Ling Yang; Yan-Qing Duan; Xiao-Yang Zhi (Current Microbiology, 2025)

The mouse resource at National Resource Center for Mutant Mice of China - Bingzhou Han; Dongshen Chen; Zhong Chen; Ting Wang; Kaiyuan Zi; Rui Feng; Xiaoliu Yang; Ling’en Li; Juan Liang; Xiang Gao (Mammalian Genome, 2025)

Riverine network size determined major driving factors of the composition and diversity of aquatic invertebrate communities in a multi-tributary mountain river basin - Chao Chang; Mi Ren; Han Wang; Sisi Ye; Xiaofeng Tang; Ding He; En Hu; Ming Li; Baozhu Pan (Water Research, 2025)

Singular value decomposition of near-field electromagnetic data for compressing and accelerating deep neural networks in the prediction of geometric parameters for through silicon via array - Song-En Chen; Eugene Su; Chih-Chung Wang; Jia-Han Li; Chao-Ching Ho (Computer Physics Communications, 2025)

Tuning the Structures and Photophysical Properties of D1-A-π-D2 Fluorophores by Terminal Donors (D2) - Dong-En Wu; Qing-Hui Guo; Jia-Han Wu; Xue-Lian Li (Journal of Fluorescence, 2025)

Construction of activated carbon/activated carbon fibre capacitive deionization composite electrode and its potential application in desalination of brackish water - Tongtong Huang; Xiaomei Dong; Weixiong Huang; Jianfeng Song; Qingsong Zheng; Zhaoyang Li; Yu Han; En Xie; Shimin Wang; Yuhui Yang; Zhanming Tan (Desalination, 2025)

Ultrasound-Targeted β-Catenin Gene Therapy Improves the Cardiac Function in Mice After Myocardial Infarction - Lei Yang; Tong Gao; Yu Huang; Pei-he Wang; Xin-hao Han; Jie Wu; Lei Huang; Qing-en Da; Kun-fu Ouyang; Zhen Han; Hai Tian; Lu Sun (Cardiovascular Toxicology, 2025)

Exploring the effects of pemetrexed on drug resistance mechanisms in human lung adenocarcinoma and its association with PGRMC1 - Ssu-Yun Wu; En-Chi Liao; Yueh-Feng Wen; Yi-Shiuan Wang; Han Meng; Hsiu-Chuan Chou; Hong-Lin Chan (Chemico-Biological Interactions, 2024)

Source characterization of the December 2018 Anak Krakatau volcano sector collapse - Xinghui Huang; Po Chen; En-Jui Lee; Xuejun Han; Li Sun; Qiang Xu (Natural Hazards, 2024)

Developing a sustainable assessment framework for identifying industrial water suitability: Perspective on the water-energy-food nexus - En Hua; Xinxueqi Han; Bernard A. Engel; Jiajie Guan; Shikun Sun; Pute Wu; Bing Wang; Yubao Wang (Agricultural Systems, 2024)

Seasonally Changing Interactions of Species Traits of Termites and Trees Promote Complementarity in Coarse Wood Decomposition - Chao Guo; Bin Tuo; Sebastian Seibold; Hang Ci; Bi‐Le Sai; Han‐Tang Qin; En‐Rong Yan; Johannes H. C. Cornelissen (Ecology Letters, 2024)
Complementary resource use by functionally different species may accelerate ecosystem processes. However, how co‐variation in plant traits and animal traits promotes complementarity through temporal plant–animal interactions is poorly understood, even less so in detrital systems, thereby hampering our fundamental understanding of decomposition and carbon turnover. We hypothesised that, in seasonal subtropical forests where termites are major deadwood decomposers, trait complementarity of both termite species and tree species should promote overall deadwood decomposition through different seasons and years. Findings from a four‐year coarse wood decomposition experiment involving 27 tree and 5 termite species support this hypothesis. Phenological and mandibular traits of the two most abundant termite species controlled wood decomposition of tree species differing in wood traits, through the seasons over 4 years, thereby promoting overall deadwood decomposition rates. Our findings indicate that complementarity in functional trait co‐variation in plants and animals plays an important role in carbon cycling.

Lateral carbon export of macroalgae and seagrass from diverse habitats contributes particulate organic carbon in the deep sea of the Northern South China Sea - Yu-En Chang; Chin-Hsin Liao; Hsueh-Han Hsieh; Vicente Gradngay Abedneko; Chin-Chang Hung; Tse-Min Lee (Marine Pollution Bulletin, 2024)

Assessing CO2 sources and sinks in and around Taiwan: Implication for achieving regional carbon neutrality by 2050 - Chin-Chang Hung; Hsueh-Han Hsieh; Wen-Chen Chou; En-Chi Liu; Chun Hoe Chow; Yi Chang; Tse-Min Lee; Peter Hans Santschi; R.R.M.K.P. Ranatunga; Hernando P. Bacosa; Yung-Yen Shih (Marine Pollution Bulletin, 2024)

Phytoremediation performance of mixed planting patterns and the associated rhizosphere microbial community in pilot-scale constructed wetlands - Yue Zhang; Yu Han; En Xie; Xingpeng Wang; Yuhui Yang; Fengcong Jia (Chemosphere, 2024)

Development of a method to assess synergy and competition for water use among water-energy-food nexus in the Yellow River basin: Water quantity-quality dimensions - Xinxueqi Han; En Hua; Jiajie Guan; Bernie A Engel; Rong Liu; Yawen Bai; Shikun Sun; Yubao Wang (Journal of Hydrology, 2024)

Versatile MOF-based nanofibrous heterostructures for engineering the CO2 photoreduction activity and selectivity: From CO to C2H5OH - Xu-Chao Xia; Feng Cheng; Peng Sun; Amare Aregahegn Dubale; Hao Han; En-Tian Cui; Jun Song; Xiu-Li Yang; Ming-Hua Xie (Chemical Engineering Journal, 2024)

Developing a framework taking into account negative environmental impacts to evaluate water-energy-food coupling efficiency - Jiajie Guan; Xinxueqi Han; Bernard A. Engel; En Hua; Shikun Sun; Pute Wu; Yubao Wang (Journal of Cleaner Production, 2024)

Quaternary integrative stratigraphy, biotas, and paleogeographical evolution of the Qinghai-Tibetan Plateau and its surrounding areas - Yong Wang; Mianping Zheng; Yuan Ling; Shuyuan Xiang; Zhaogang Shao; Kexin Zhang; Xue Ke; Xiao Lin; Fang Han; Jian’en Han (Science China Earth Sciences, 2024)

Distribution and adsorption-desorption of organophosphate esters from land to sea in the sediments of the Beibu Gulf, South China Sea: Impact of seagoing river input - Fang Liu; Ruijie Zhang; Haolan Li; Huanxin Liu; Annan Yan; Minwei Han; Yaru Kang; Zheng-en Zhang; Yinghui Wang; Kefu Yu (Science of The Total Environment, 2024)

Nitrite determination in food using electrochemical sensor based on self-assembled MWCNTs/AuNPs/poly-melamine nanocomposite - En Han; Lei Li; Ting Gao; Yingying Pan; Jianrong Cai (Food Chemistry, 2024)

Corrigendum to “Source area morphometry and high depletion rate of landslides may indicate their coseismic origin” [Engineering Geology 330 (2024) 107424] - Ivo Baroň; Jan Jelének; Jan Klimeš; Jia-Jyun Dong; Rostislav Melichar; Martin Šutjak; Yichin Chen; Che-Ming Yang; En-Lun Zhang; Joanna Méndez; Chia-Han Tseng; Filip Hartvich; et al. (Engineering Geology, 2024)

Source area morphometry and high depletion rate of landslides may indicate their coseismic origin - Ivo Baroň; Jan Jelének; Jan Klimeš; Jia-Jyun Dong; Rostislav Melichar; Martin Šutjak; Yichin Chen; Che-Ming Yang; En-Lun Zhang; Joanna Méndez; Chia-Han Tseng; Filip Hartvich; et al. (Engineering Geology, 2024)

Sensitivity analysis and process optimization for biomass processing in an integrated gasifier-solid oxide fuel cell system - Hafiz Hamza Faheem; Ben Britt; Mateus Rocha; Shou-Han Zhou; Chao'en Li; Weiwei Cai; Liyuan Fan (Fuel, 2024)

Bisphenol A detection based on nano gold-doped molecular imprinting electrochemical sensor with enhanced sensitivity - En Han; Yingying Pan; Lei Li; Jianrong Cai (Food Chemistry, 2023)

Simultaneous detection of mixed pesticide residues based on portable Raman spectrometer and Au@Ag nanoparticles SERS substrate - Lixin Ma; En Han; Limei Yin; Qian Xu; Caixia Zou; Junwen Bai; Wei Wu; Jianrong Cai (Food Control, 2023)

Human TRMT1 catalyzes m2G or m22G formation on tRNAs in a substrate-dependent manner - Qing-Ping Xiong; Jing Li; Hao Li; Zhi-Xuan Huang; Han Dong; En-Duo Wang; Ru-Juan Liu (Science China Life Sciences, 2023)

Mitochondrial RNA m3C methyltransferase METTL8 relies on an isoform-specific N-terminal extension and modifies multiple heterogenous tRNAs - Meng-Han Huang; Jin-Tao Wang; Jian-Hui Zhang; Xue-Ling Mao; Gui-Xin Peng; Xiuying Lin; Daizhu Lv; Chen Yuan; Huan Lin; En-Duo Wang; Xiao-Long Zhou (Science Bulletin, 2023)

Long non-coding RNA in coronary artery disease: the role of PDXDC1-AS1 and SFI1-AS1 - Shu He; Sheng Zhang; Yan-Jun Wang; Xiong-Kang Gan; Jia-Xin Chen; Han-Xiao Zhou; En-Zhi Jia (Functional & Integrative Genomics, 2023)

Can the mix-charged NF membrane directly obtained by the interfacial polymerization of PIP and TMC? - Qiu-Yu Zhu; Zi-Yun Xu; Jie-Han Fu; Jie Huang; Zhen-Liang Xu; Min Tong; En-Chao Li; Yong-Jian Tang (Desalination, 2023)

Ionic liquid modified COF nanosheet interlayered polyamide membranes for elevated nanofiltration performance - Shuangqiao Han; Wenhui You; Shihao Lv; Chaojun Du; Xiang Zhang; En Zhang; Junyong Zhu; Yatao Zhang (Desalination, 2023)

Visible light-triggered smart photoreversible color switching systems based on VOx QDs for constructing smart corrosion resistant coatings on AA2024-T3 - Sharjeel Ahmed; Hongwei Shi; Ningjie Gao; Fuchun Liu; Izuchukwu K. Nwokolo; Jiwen Li; Wanyu Zhang; Mustehsin Ali; Imran Ali; En-Hou Han (Chemical Engineering Journal, 2023)

Decreased Plasma Pituitary Adenylate Cyclase Activating Polypeptide (PACAP) Levels are Linked with Disease Severity in Patients with Liver Cirrhosis - Lian-Ying Yang; Ji-Ping Hou; En-Kun Han; Gang Qiao; Li-Bin Liu; Xue-Bo Men (International Journal of Peptide Research and Therapeutics, 2021)

Occurrence, distribution, and partitioning of antibiotics in surface water and sediment in a typical tributary of Yellow River, China - Linfang Wang; Hua Li; Jinhua Dang; Hong Guo; Yu’en Zhu; Wenhui Han (Environmental Science and Pollution Research, 2021)

Large Deformation Control of Deep Roadways in Fractured Hard Rock Based on Cracking-Restraint Method - Yue-Mao Zhao; Xia-Ting Feng; Quan Jiang; Yong Han; Yang-Yi Zhou; Hui-Gao Guo; Yong-Yuan Kou; Ying-En Shi (Rock Mechanics and Rock Engineering, 2021)

The youngest matrix of 234 Ma of the Kanguer accretionary mélange containing blocks of N-MORB basalts: constraints on the northward subduction of the Paleo-Asian Kanguer Ocean in the Eastern Tianshan of the Southern Altaids - Songjian Ao; Qigui Mao; Brian F. Windley; Dongfang Song; Zhiyong Zhang; Ji’en Zhang; Bo Wan; Chunming Han; Wenjiao Xiao (International Journal of Earth Sciences, 2021)

Timing of coseismic displacement grid model construction for updating the semi-kinematic reference frame: case study in Taiwan - Shih-Han Hsiao; Kuo-En Ching; Kwo-Hwa Chen; Chien-Kuan Li (Journal of Geodesy, 2021)

Makran ophiolitic basalts (SE Iran) record Late Cretaceous Neotethys plume-ridge interaction - Rasoul Esmaeili; Wenjiao Xiao; Mohammad Ebrahimi; Ji’En Zhang; Zhiyong Zhang; Yasser Abd El-Rahman; Chunming Han; Bo Wan; Songjian Ao; Dongfang Song; Shirin Shahabi; Arthur Aouizerat (International Geology Review, 2020)

Mesorhizobium rhizophilum sp. nov., a 1-aminocyclopropane-1-carboxylate deaminase producing bacterium isolated from rhizosphere of maize in Northeast China - Jun-lian Gao; Jing Xue; Yu-chen Sun; Han Xue; En Tao Wang; Hui Yan; Shuai Tong; Li-wei Wang; Xiuhai Zhang; Jian-guang Sun (Antonie van Leeuwenhoek, 2020)

Accretionary processes and metallogenesis of the Central Asian Orogenic Belt: Advances and perspectives - Wenjiao Xiao; Dongfang Song; Brian F. Windley; Jiliang Li; Chunming Han; Bo Wan; Ji’en Zhang; Songjian Ao; Zhiyong Zhang (Science China Earth Sciences, 2020)

The tectono-magmatic evolution of the West Junggar terrane (NW China) unravelled by U–Pb ages of detrital zircons in modern river sands - Bo Liu; Bao-Fu Han; En-Pu Gong; Jia-Fu Chen (International Geology Review, 2019)

Expression and characterisation of a pH and salt tolerant, thermostable and xylose tolerant recombinant GH43 β-xylosidase from Thermobifida halotolerans YIM 90462T for promoting hemicellulose degradation - Yi-Rui Yin; Wen-Dong Xian; Ming-Xian Han; En-Min Zhou; Lan Liu; Dalal Hussien M. Alkhalifah; Wael N. Hozzein; Min Xiao; Wen-Jun Li (Antonie van Leeuwenhoek, 2019)

Evolutionary dynamics of transposable elements during silkworm domestication - Min-Jin Han; Hong-En Xu; Xiao-Min Xiong; Hua-Hao Zhang (Genes & Genomics, 2018)

Linking intraspecific trait variability and spatial patterns of subtropical trees - En-Rong Yan; Liu-Li Zhou; Han Y. H. Chen; Xi-Hua Wang; Xiang-Yu Liu (Oecologia, 2018)

Anatomy of composition and nature of plate convergence: Insights for alternative thoughts for terminal India-Eurasia collision - WenJiao Xiao; SongJian Ao; Lei Yang; ChunMing Han; Bo Wan; Ji’En Zhang; ZhiYong Zhang; Rui Li; ZhenYu Chen; ShuaiHua Song (Science China Earth Sciences, 2017)

Rhizobium hidalgonense sp. nov., a nodule endophytic bacterium of Phaseolus vulgaris in acid soil - Jun Yan; Hui Yan; Li Xue Liu; Wen Feng Chen; Xiao Xia Zhang; Myrthala M. Verástegui-Valdés; En Tao Wang; Xiao Zeng Han (Archives of Microbiology, 2017)

Advances on Bioactive Polysaccharides from Medicinal Plants - Jian-Hua Xie; Ming-Liang Jin; Gordon A. Morris; Xue-Qiang Zha; Han-Qing Chen; Yang Yi; Jing-En Li; Zhi-Jun Wang; Jie Gao; Shao-Ping Nie; Peng Shang; Ming-Yong Xie (Critical Reviews in Food Science and Nutrition, 2016)

Late Devonian–early Permian accretionary orogenesis along the North Tianshan in the southern Central Asian Orogenic Belt - Chao Li; Wenjiao Xiao; Chunming Han; Kefa Zhou; Ji’en Zhang; Zhixin Zhang (International Geology Review, 2015)

A fracture enhancement method based on the histogram equalization of eigenstructure-based coherence - Xi-Ying Dou; Li-Guo Han; En-Li Wang; Xue-Hua Dong; Qing Yang; Gao-Han Yan (Applied Geophysics, 2014)

Purification and characterization of a new alginate lyase from a marine bacterium Vibrio sp. - Ya Wang; En-Wen Guo; Wen-Gong Yu; Feng Han (Biotechnology Letters, 2013)

Detection of Human Bocavirus-2 in children with acute Gastroenteritis in South Korea - Tae-Hee Han; Cheol-Hwan Kim; Sang-Hun Park; En-Jung Kim; Ju-Young Chung; Eung-Soo Hwang (Archives of Virology, 2009)

Unique community structure and biogeography of soybean rhizobia in the saline-alkaline soils of Xinjiang, China - Li Li Han; En Tao Wang; Tian Xu Han; Jie Liu; Xin Hua Sui; Wen Feng Chen; Wen Xin Chen (Plant and Soil, 2009)

Genetic diversity of rhizobia associated with Vicia faba in three ecological regions of China - Chang Fu Tian; En Tao Wang; Tian Xu Han; Xin Hua Sui; Wen Xin Chen (Archives of Microbiology, 2007)

Sequencing and Amplified Restriction Fragment Length Polymorphism Analysis of Ribonucleotide Reductase Large Subunit Gene of the White Spot Syndrome Virus in Blue Crab (Callinectes sapidus) from American Coastal Waters - Yun-Shiang Chang; Shao-En Peng; Han-Ching Wang; Hui-Chen Hsu; Ching-Hui Ho; Chung-Hsiung Wang; Sho-Ya Wang; Chu-Fang Lo; Guang-Hsiung Kou (Marine Biotechnology, 2001)